Measuring the distance between quantum many-body wave functions. (6th July 2018) - Chen, Xiao; Zhou, Tianci; Xu, Cenke
Abstract: We study the distance of two wave functions under chaotic time evolution. The two initial states differ only by a local perturbation. To be entitled 'chaos' the distance should have a rapid growth afterwards. Instead of focusing on the entire wave function, we measure the distance d 2 ( t ) by investigating the difference of two reduced density matrices of the subsystem A that is spatially separated from the local perturbation. This distance d 2 ( t ) grows with time and eventually saturates to a small constant. We interpret the distance growth in terms of operator scrambling picture, which relates d 2 ( t ) to the square of commutator (out-of-time-order correlator) and shows that both these quantities measure the area of the operator wave front in subsystem A . Among various one-dimensional spin- models, we numerically show that the models with non-local power-law interaction can have an exponentially growing regime in d 2 ( t ) when the local perturbation and subsystem A are well separated. This so-called Lyapunov regime is absent in the spin- chain with local interaction only. After sufficiently long time evolution, d 2 ( t ) relaxes to a small constant, which decays exponentially as we increase the system size and is consistent with eigenstate thermalization hypothesis. Based on these results, we demonstrate that d 2 ( t ) is a useful quantity to characterize both quantum chaos and quantum thermalization in many-body wave functions.